2016
DOI: 10.1101/071464
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The impact of chromatin dynamics on Cas9-mediated genome editing in human cells

Abstract: In order to efficiently edit eukaryotic genomes, it is critical to test the impact of chromatin dynamics on CRISPR/Cas9 function and develop strategies to adapt the system to eukaryotic contexts. So far, research has extensively characterized the relationship between the CRISPR endonuclease Cas9 and the composition of the RNA-DNA duplex that mediates the system's precision. Evidence suggests that chromatin modifications and DNA packaging can block eukaryotic genome editing by custom-built DNA endonucleases lik… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
58
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(61 citation statements)
references
References 34 publications
(46 reference statements)
3
58
0
Order By: Relevance
“…dCas9 binding and SpCas9 nuclease activity have previously been shown to correlate with an absence of repressive histone marks and increased DNase I sensitivity in human cancer cells. This was shown by Chen et al .…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…dCas9 binding and SpCas9 nuclease activity have previously been shown to correlate with an absence of repressive histone marks and increased DNase I sensitivity in human cancer cells. This was shown by Chen et al .…”
mentioning
confidence: 96%
“….and Daer et al . using inducible model systems, and by Chari et al . using a library‐on‐library approach.…”
mentioning
confidence: 99%
“…Importantly, all these potential cleavage sites map specifically to various types of ERV sequences, while off‐target sites were not detected in the CHO genome. Although these sgRNA sequences contain a multitude of predicted target sites, we hypothesized that expressed ERVs might be preferentially cleaved by the CRISPR‐Cas9 nuclease, due to the more efficient cleavage of open chromatin (Daer, Cutts, Brafman, & Haynes, ).…”
Section: Resultsmentioning
confidence: 99%
“…Several authors showed that Cas9 cleavage efficiency positively correlates with open chromatin based on DNase I hypersensitivity. Along the same line, the activity of Cas9 can be significantly hindered by compact heterochromatin in cells [21]. Interestingly, the engineered Cas9 variants designed to improve specificity, Cas9-HF1 [22] and eSpCas9(1.1) [23], might be even more impacted than Cas9 by the chromatin-related factors [24].…”
Section: Analysis Of the Target Locusmentioning
confidence: 99%
“…While treatment with chromatin-disrupting drugs does not appear sufficient, transient overexpression of a targeted transcriptional activator might be an effective method to enhance Cas9 editing at closed chromatin regions [21]. …”
Section: Analysis Of the Target Locusmentioning
confidence: 99%